2016
DOI: 10.1016/j.neulet.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism related differences in the functional neuroanatomical correlates of multitasking. An fMRI study

Abstract: It is known that neuroticism impairs cognitive performance mostly in difficult tasks, but not so much in easier tasks. One pervasive situation of this type is multitasking, in which the combination of two simple tasks creates a highly demanding dual-task, and consequently high neurotics show higher dual-task costs than low neurotics. However, the functional neuroanatomical correlates of these additional performance impairments in high neurotics are unknown. To test for this, we assessed brain activity by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Alterations in structure and functional activity within the IFG in individuals with higher neuroticism were also reported by other studies and may represent the neural correlate of the reduced ability for the cognitive regulation of emotions (Bjørnebekk et al, 2013;Sosic-Vasic et al, 2012). Other studies have found alterations in connectivity and brain activity in MFG, midFG and, more generally, in the prefrontal cortex (Forbes et al, 2014;Szameitat et al, 2016;Tzschoppe et al, 2014). Alterations of the LFO metrics were also found in the DMN network confirming the relative vast literature linking DMN alterations to neuroticism (Sampaio et al, 2014;Wei et al, 2011;Wei et al, 2016).…”
Section: Lfo Metrics (Alff-falff)supporting
confidence: 60%
See 1 more Smart Citation
“…Alterations in structure and functional activity within the IFG in individuals with higher neuroticism were also reported by other studies and may represent the neural correlate of the reduced ability for the cognitive regulation of emotions (Bjørnebekk et al, 2013;Sosic-Vasic et al, 2012). Other studies have found alterations in connectivity and brain activity in MFG, midFG and, more generally, in the prefrontal cortex (Forbes et al, 2014;Szameitat et al, 2016;Tzschoppe et al, 2014). Alterations of the LFO metrics were also found in the DMN network confirming the relative vast literature linking DMN alterations to neuroticism (Sampaio et al, 2014;Wei et al, 2011;Wei et al, 2016).…”
Section: Lfo Metrics (Alff-falff)supporting
confidence: 60%
“…However, we found positive correlation between REHO and neuroticism in the prefrontal cortex (SFG, MFG, MidFG), in the fusiform gyrus and in precuneus. As mentioned, the prefrontal cortex and DMN areas including the precuneus were found to be modulated by neuroticism both in resting state analysis, as well as during task (Forbes et al, 2014;Sampaio et al, 2014;Szameitat et al, 2016;Tzschoppe et al, 2014;Wei et al, 2011;Wei et al, 2016). As far as the fusiform gyrus is concerned, Kruschwitz and colleagues showed an altered amygdala-fusiform gyrus connectivity in individuals with higher neuroticism (Kruschwitz et al, 2014).…”
Section: Rehomentioning
confidence: 91%
“…This study also supported the idea that high neurotics invest less mental resources into the task. They showed that brain activation in the lateral-prefrontal cortex, which was specific to multitasking, was lower in high than in low neurotics [29]. Several studies used other paradigms, such as the n-back task [30], the go-no-go task [31], the delayed-response working memory task [32], and the probe task [33,34] to investigate neuroticism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the level of their performance has an overwhelming impact in the economy. Neurotic entrepreneurs have increasingly negative effects on performance as the business gets harder and more complex (Szameitat, Saylik and Parton 2016). On the other hand, emotional stability has increasingly positive effects as pressure increases.…”
Section: Introductionmentioning
confidence: 99%